Potential of resistance inducers for citrus huanglongbing management via soil application and assessment of induction of pathogenesis-related protein genes - Arya Widyawan; Mohammed A. Al-Saleh; Mahmoud H. El Komy; Hathal M. Al Dhafer; Yasser E. Ibrahim (Heliyon, 2023)
Huanglongbing (HLB) or citrus greening currently is the most devastating citrus disease worldwide. Unfortunately, no practical cure has been available up to now. This makes the control of HLB as early as possible very important to be conducted. The objective of this study was to investigate the efficacy of the application of salicylic acid (SA) and Phenylacetic acid (PAA) on one-year-old seedlings of different citrus species (Citrus reticulata, C. sinensis, C. aurantifolii) growing on C. volkameriana and C. aurantium by soil drench methods. Factorial analysis of variance showed the percent change in “Candidatus Liberibacter asiaticus” titer and disease severity on a different combination of citrus species growing on the two rootstocks treated with inducers and Oxytetracycline (OTC) were significantly different compared to the untreated plants. SA alone or in combination with OTC provided excellent (P-value < 0.05) control of HLB based on all parameters. The interaction between both factors (Rootstocks x Citrus species) significantly influenced the Ct value (P-value = 0.0001). “Candidatus Liberibacter asiaticus” titer in plants treated with OTC was reduced significantly with a range of −18.75 up to −78.42. Overall, the highest reduction was observed in the application of OTC on sweet orange growing on C. volkameriana (−78.42), while the lowest reduction was observed in the same cultivar which was treated with a combination of SA and OTC (−3.36). Induction of pathogenesis-related (PR) genes, i.e., PR1, PR2, and PR15, biosynthesis of Jasmonic acid and ethylene which are also important pathways to defense activity were also significantly increased in treated plants compared to untreated plants. This study suggests that the application of inducer alone is acceptable for HLB management. We proposed the application of SA and PAA as a soil drench on the citrus seedlings as promising, easy, and environmentally safe for HLB disease control on citrus seedlings.